2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

FreiHAND: A Dataset for Markerless Capture of Hand Pose and Shape From Single RGB Images

Abstract: Estimating 3D hand pose from single RGB images is a highly ambiguous problem that relies on an unbiased training dataset. In this paper, we analyze cross-dataset generalization when training on existing datasets. We find that approaches perform well on the datasets they are trained on, but do not generalize to other datasets or in-the-wild scenarios. As a consequence, we introduce the first large-scale, multi-view hand dataset that is accompanied by both 3D hand pose and shape annotations. For annotating this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
369
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(380 citation statements)
references
References 35 publications
2
369
0
Order By: Relevance
“…This favors learning priors, to hallucinate the invisible keypoints, over measuring their location diminishing performance in the subsequent 3D lifting step. To circumvent the problem, FreiPose extracts features f i ∈ R H3×W3×C rather than keypoints from the cropped images I c,i ∈ R H2×W2×3 and deploys a differentiable inverse projection operation Π −1 [30], which maps features into a 3D representation…”
Section: Motion Capturementioning
confidence: 99%
“…This favors learning priors, to hallucinate the invisible keypoints, over measuring their location diminishing performance in the subsequent 3D lifting step. To circumvent the problem, FreiPose extracts features f i ∈ R H3×W3×C rather than keypoints from the cropped images I c,i ∈ R H2×W2×3 and deploys a differentiable inverse projection operation Π −1 [30], which maps features into a 3D representation…”
Section: Motion Capturementioning
confidence: 99%
“…FreiHand [140] is a multi-view RGB dataset containing hand-object interactions. In total, it encompasses 134 K samples at 224 × 224 resolution, 130 K for training and 4 K for evaluation.…”
Section: Datasetsmentioning
confidence: 99%
“…Hand pose estimation has been a major research area in the computer vision field, and it has benefited considerably from the rise of deep learning. Especially, hand pose estimation using a single color image as DeepFisheye, is an active re search area [3,47,63,72,78,82]. Zimmermann et al [81] suggested a deep learning pipeline that segments a hand in an image, identifies keypoints, and finally estimates the most likely hand pose.…”
Section: D Hand Pose Estimation Using a Cameramentioning
confidence: 99%
“…For a more accurate evaluation, we require more accurate ground truth data. The possible options that we will consider in our future work include using a multi-camera system [82] and a manual annotation method [48].…”
Section: Limitations and Future Workmentioning
confidence: 99%